Development of Die Sinking EDM E-Learning Module for Online Learning - Azhar, Muhammad Syakirin; Rohanai, Reyanhealme (Research and Innovation in Technical and Vocational Education and Training, 2024)
Electronic modules known as e-learning module is the development of printed modules in digital displays which are widely adapted from printed modules.  However, there is still the issue of a few students having difficulty getting complete and conducive notes. Therefore, this study aims to develop an e-learning module for the topic of EDM Die Sinking. The main software that is Google Sites has been used to produce this e-learning module. In this study, the researcher used the ADDIE  model as a guide and reference throughout the development process of this e-learning module. This study involved five experts consisting of four lecturers from Universiti  Tun Hussein Onn Malaysia and one teacher from Batu Lanchang Vocational College.  The expert verification form was used as an instrument by the researcher in this study.  The expert evaluation of this e-learning module includes two aspects that need to be evaluated, namely the e-module design and content. The evaluation is analyzed through expert verification to obtain functionality, The results of the study show that a large number of items evaluated from these two aspects have the approval of more than 80 percent of this e-learning module can be used in the teaching and learning process.